2011
DOI: 10.5021/ad.2011.23.s2.s261
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Auricular Ossification

Abstract: Ectopic ossification refers to the process of new bone formation in sites that normally do not ossify. The auricle is composed of elastic cartilage, and hence is a pliable structure. Auricular ossification is a rare condition that might be caused by injurious processes, including frostbite, physical trauma, and inflammation as well as processes related to metabolic or endocrine disorders. Here, we report a case of unilateral auricular ossification in a 53-year-old Korean man who had previously rubbed his ear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Studies to address the identification of auricular calcifications/ossifications amid CT scans according to our methods [7,15]. Overall, the data coming from our sample-based analysis via isolated case reports (N = 49 subjects) showed that X-ray and/or CT confirmation was done in all cases (no differences were noted in imagery approaching the patients with an endocrine [1,6,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] versus non-endocrine [2,4,7,9,12,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]…”
Section: Imagery Assessments Amidst Identifying a Petrified Earmentioning
confidence: 92%
See 3 more Smart Citations
“…Studies to address the identification of auricular calcifications/ossifications amid CT scans according to our methods [7,15]. Overall, the data coming from our sample-based analysis via isolated case reports (N = 49 subjects) showed that X-ray and/or CT confirmation was done in all cases (no differences were noted in imagery approaching the patients with an endocrine [1,6,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] versus non-endocrine [2,4,7,9,12,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]…”
Section: Imagery Assessments Amidst Identifying a Petrified Earmentioning
confidence: 92%
“…Table 2. Sample-focused analysis on petrified ear in subjects apparently without any endocrine conditions (according to the original reports); the display starts with the most recent publication date [2,4,7,9,12,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Abbreviations: B/U = bilateral or unilateral PE; C1, C2 = case 1 or 2 (patients from case series); CT = computed tomography; F = female; M = male; PE = petrified ear; P1, P2, or P3 = patient 1, 2, or 3 (patients from case series).…”
Section: Non-endocrine Sample-based Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of bone formation and if the cartilage itself ossifies or provides a scaffold for new bone growth is unclear. 4,5 Many patients do not have osseous coverage (1 used in our control data set) and symptoms have resolved. Therefore, it is important to remember the absence of bone formation does not imply failure of surgery.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%